Pengaruh Program Pemutihan, SAMSAT Keliling, Tingkat Pendapatan, dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus pada Kantor Bersama SAMSAT Magetan) - Fita Ristiana; Khusnatul Zulfa Wafirotin; Nursayidatul Muntiah (BAJ: Behavioral Accounting Journal, 2022)
Taxes are the largest source of revenue in Indonesia. In this modern era, motorized vehicles are needed to support the implementation of community mobility, therefore the number of motorized vehicles continues to increase, one of which is in Magetan. From 2018 to 2020 the frequency of motorized vehicles in Magetan continues to increase. Even though the frequency of motorized vehicles in Magetan is getting higher, there are still tax objects that are not/unpaid. A total of 29,230 tax objects are still owed in Magetan. The government continues to try to maximize regional revenues. The purpose of this research is to examine the effect of the whitening program, mobile SAMSAT, income level, and tax sanctions simultaneously or partially on the compliance of motorized vehicle taxpayers in SAMSAT Magetan simultaneously or partially. The population that the researchers set was taxpayers in SAMSAT Magetan. Determination of the sample using non-probability sampling technique and incidental sampling (accidental sampling). The type of data is primary data. Determination of sample size using the slovin formula then obtained the results of 100 samples. The results explain partially and simultaneously (simultaneous) the tax exemption program, SAMSAT roving, income levels, and tax sanctions that positively and significantly affect the compliance of motorized vehicle taxpayers.